2021
DOI: 10.1111/apt.16525
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of drug survival: A cohort study comparing anti‐tumour necrosis factor agents using the Swedish inflammatory bowel disease quality register

Abstract: Summary Background Whether long‐term effectiveness differs between anti‐tumour necrosis factor (anti‐TNF) agents is unknown. Aims To examine drug survival of first‐line anti‐TNF agents and identify predictors of discontinuation. To reduce channelling bias, we also compared drug survival of the second anti‐TNF. Methods Biologic‐naïve patients (N = 955) recorded in the Swedish IBD Quality Register (SWIBREG) were examined. We used propensity score matching, comparing drug survival over up to three years of follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…In the absence of head-to-head comparisons, the retrospective evaluation of real-world data is an accepted approach for comparing drug efficacy. DS has been increasingly used as a surrogate for treatment efficacy when evaluating different therapeutic agents in a real-world setting [ 7 , 8 , 9 ]. It measures continuing medication prescription based on ongoing therapeutic efficacy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the absence of head-to-head comparisons, the retrospective evaluation of real-world data is an accepted approach for comparing drug efficacy. DS has been increasingly used as a surrogate for treatment efficacy when evaluating different therapeutic agents in a real-world setting [ 7 , 8 , 9 ]. It measures continuing medication prescription based on ongoing therapeutic efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, it reflects real-world practice that allows for treatment optimization, including dose adjustments. The rate of failure and duration of DS for various drugs are different and provide important comparative efficacy data given the paucity of head-to-head trials of advanced therapies in UC [ 7 , 9 ]. DS data, in some respects, may be even more informative than head-to-head trials by more closely resembling real-world practice.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that less than half of all patients with CD who initiate first-line anti-TNF treatment in Sweden continue the drug after 3 years [ 25 ]. Accordingly, many patients require sequential therapies over their disease course.…”
Section: Discussionmentioning
confidence: 99%
“…5) Some studies have assessed real-world drug survival (DS) rates, long-term effectiveness, and safety of biologics. 6,7) The DS time is the duration of treatment with a drug, where a high value indicates high overall acceptability, including the effectiveness and safety of the drug. Therefore, DS studies are useful for evaluating long-term treatments for chronic diseases in specialties such as rheumatology, der-matology, and gastroenterology.…”
Section: Introductionmentioning
confidence: 99%